Patient and physician factors influence decision-making in hypercholesterolemia: a questionnaire-based survey - Krempf, Michel (Lipids Health Dis, 2015)
BACKGROUND: Goal attainment of guideline-recommended low-density lipoprotein cholesterol (LDL-C) is suboptimal. Little is known about how patient factors influence physicians’ treatment decision-making in hypercholesterolemia. We examined physicians’ treatment recommendations in high-risk patients whose LDL-C remained uncontrolled despite statin monotherapy. METHODS: Physicians completed a questionnaire prior to randomization into period I of a two-period randomized controlled trial evaluating LDL-C goal attainment in patients whose LDL-C remained ≥100 mg/dL after 5 weeks’ treatment with atorvastatin 10 mg/day (NCT01154036). Physicians’ treatment recommendations were surveyed for two hypothetical and one real scenario: (1) LDL-C presumed near goal (between 100–105 mg/dL), (2) LDL-C presumed far from goal (~120 mg/dL), and (3) observed baseline LDL-C of enrolled patients. Prognostic factors considered during decision-making were identified by regression analysis. Observed lipid outcomes at the end of period I (following 6 weeks’ treatment with ezetimibe 10 mg plus atorvastatin 10 mg, atorvastatin 20 mg, or rosuvastatin 10 mg) were compared with estimated LDL-C outcomes for physicians’ treatment recommendations after 6 weeks (based on individual patients’ pre-randomization LDL-C and expected incremental change). RESULTS: Questionnaires were completed for 1,534 patients. No change in therapy, or double atorvastatin dose, were frequently recommended, even when LDL-C was far from goal (6.5% and 52.2% of patients, respectively). Double atorvastatin dose was commonly recommended in all scenarios (43–52% of patients). More intensive LDL-C-lowering regimens were recommended infrequently e.g. double atorvastatin dose and add ezetimibe only <12% in all scenarios. Overall, cardiovascular risk factors and desire to achieve a more aggressive LDL-C goal were prominent factors in decision-making for treatment. Comparison of observed and estimated LDL-C levels showed that physicians tended to overestimate the effectiveness of their recommendations. CONCLUSIONS: This study provides insight into physicians’ perspectives on clinical management of hypercholesterolemia and highlights a gap in knowledge translation from guidelines to clinical practice. The need for lower LDL-C and cardiovascular risk were key drivers in clinical decision-making, but physicians’ treatment choices were more conservative than guideline recommendations, potentially resulting in poorer LDL-C reduction. When compared with actual outcomes, projected LDL-C control was better if physicians used more comprehensive strategies rather than simply doubling the statin dose. TRIAL REGISTRATION: Clinicaltrials.gov: NCT01154036 ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12944-015-0037-y) contains supplementary material, which is available to authorized users.